1860 Kan. Sess. Laws 137, An Act to Amend and Consolidate the Several Act Relating to the City of Lawrence, § 35, pt. 7 - (:unkn) unknown (General Publisher, 1860)
Granted the city of Lawrence the authority to regulate the keeping and conveying of gun powder and other combustible and dangerous materials.
--
Keywords: GUN POWDER STORAGE